Metastatic Malignant Melanoma Clinically Presenting as Parotid Mass - A Case Report of an Unusual Clinical Presentation - Naseem, Maria; Asif, Muhammad; Khadim, Muhammad Tahir; din, Hafeez ud; Shoaib, Iman (Pakistan Armed Forces Medical Journal, 2022)
Malignant melanoma has been considered as one of the most common tumor of the skin despite its occurrence in other organs. Being fatal in nature, timely detection and subsequent treatment is essential to avoid poor prognosis. The current case occurred in a 73-year-old male patient, with a melanoma presented as metastasis in parotid lymph node. The article discusses and focuses on the distinct clinic-pathologic presentation of this case, emphasizing the necessity to identify and report such cases for understanding of its molecular pathology role and impact. However, these rare lesions may present themselves in an un-common way which needs to be identified and reported to understand their biologic behavior. The current case report aims to fulfill the understanding criteria of such incidents.